Relationship between distributed leadership, quality administrative and academic processes and institutional effectiveness in public universities in Nigeria - Kayode, David Jimoh (2016)
Previous studies have shown that distributed leadership enhances the effectiveness of the university system and suggested mediating variables in future studies. However, there are limited studies about distributed leadership been carried out in Nigeria public university system. Therefore, this study examined the mediating role of quality administrative and academic processes on the relationship between distributed leadership and institutional effectiveness. The issues impeding the effectiveness of public universities in Nigeria were also explored. This study utilized a mixed method approach. The quantitative data were collected from 346 lecturers selected through a multi-stage sampling technique using a survey instrument, while eight respondents including the university’s administrators and lecturers were purposively selected for interviews using semi-structured questions from the 10 sampled public universities in five geo-political zones in Nigeria. The results showed a moderate level of distributed leadership practices, quality administrative and academic processes implementation and institutional effectiveness. The results also show that there are positive significant relationship between distributed leadership, quality administrative and academic processes and institutional effectiveness except distributed leadership which was not related to institutional effectiveness, which suggest the need for mediating variable. It was found that quality administrative and academic processes significantly mediated the relationship between distributed leadership and institutional effectiveness. The qualitative findings revealed that funding, corruption, poor mentoring and supervision, and politicization of the university system were hindering the effectiveness of public universities. It was concluded that university effectiveness can be improved through distributed leadership, quality administrative and academic processes. The study contributes to the field of distributed leadership within the context of management quality in educational institutions. The study also implies that there is a need for both practitioners and policy makers to restructure the curriculum to align with the industries and global requirement as well as implement leadership development program for university administrators in Nigeria.